Analyst following and stock price crash risk - Dong, Yue (2016)
Using a sample of 31,261 firm-year observations of US-listed firms over 1995 – 2011, this paper investigates the relation between analyst following and contemporaneous stock price crash risks. I find that analyst coverage is positively associated with firm-specific stock price crash risk. I also show that the positive association between analyst following and stock price crash risk is more pronounced for firms with greater business risks and firms with overconfident CEOs. Overall, these findings indicate that managers are incentivized to smooth out bad news disclosure and analysts’ monitoring prevents them from doing so.